Assessing species bias in amphibian research on endocrine disruptors: beyond Xenopus laevis - Martyna Frątczak; Mikołaj Kaczmarski; Katarzyna Szkudelska; Piotr Tryjanowski (Frontiers in Environmental Science)
Due to their high sensitivity to hormonal agents, in recent years, amphibians have been proposed as bioindicators for the presence of endocrine-disrupting compounds (EDCs) in the environment. EDCs are a chemically diverse group of compounds, mainly of anthropogenic origin, that can interfere with hormone receptors. The escalating global environmental pollution with endocrine-disrupting compounds (EDCs) poses a significant threat to wildlife and human health. Amphibians are at high risk of exposure to EDCs in the environment, as they produce eggs without a protective shell, possess highly permeable skin, and most of them undergo an aquatic life phase, where they are chronically exposed to EDCs in the water. This exposure raises concerns about the contribution of EDCs to the dramatic decline of amphibian populations and underscores the necessity of environmental-relevant studies in this area. Despite the critical need, amphibians have attracted relatively little research focus in this regard. Although above 200 experimental studies on the topic of EDCs and sex, reproduction, and related traits in amphibians have been conducted, a significant portion of them rely on model species from the Xenopus genus, which do not fully represent the diverse group of amphibians. Additionally, these studies often use strict laboratory conditions that fail to mimic natural exposure scenarios. Our extensive review highlights the research gaps and emphasizes the importance of incorporating a broader range of amphibian species to understand the true impact of EDCs. We advocate for more studies in environmentally relevant settings and the use of native species to enhance the ecological validity of findings.